Florā of Turkey and the East Aegean Islands (Edinburgh Edinburgh Edinburgh Edinburgh Edinburgh)
5 c. (1. c. [8], 567 s. ; 5. c. xviii, 890 s. ; 6. c. xviii, 825 s. ; 7. c. xx, 947 s. ; 8. c. xx, 632 s.)